Association between C-reactive protein and age-related macular degeneration - Borooah, Mitali; Ekka, Jayant (International Journal of Research in Medical Sciences, 2019)
Background: Age-related macular degeneration (AMD) is the leading cause of irreversible visual impairment among the elderly, worldwide affecting 30-50 million individuals. Inflammation is now increasingly thought to be a key risk factor for AMD. The association of CRP with AMD has been reported in only a few studies, with somewhat inconsistent results. The present study was undertaken to determine the association between AMD and serum CRP levels. Methods: A total of 53 patients diagnosed of any form of AMD fulfilling inclusion and exclusion criteria were included. A 5 mL sample of venous blood (non-fasting) was collected to determine serum high-sensitivity CRP levels (hsCRP). Different stages of AMD and serum hs CRP level were compared using one-way ANOVA test and calculated p value <0.05 was considered as statistically significant. Comparison between the two groups, one with risk factor and one without risk factor was performed using student-t test and calculated p value <0.05 was considered statistically significant. Results: Out of 53 patients 21 were having early AMD, 21 were having intermediate AMD and 11 were having advanced AMD. The mean serum hs CRP level was 0.14±0.05 mg/dL, 0.20±0.09 mg/dL and 0.28±0.08 mg/dL in early, intermediate and advanced AMD respectively. When statistically analysed the difference of mean serum hs CRP level among the three groups was found to be statistically significant. Conclusions: Type of AMD influence the baseline hsCRP level. Smoking and diabetes are associated with higher baseline serum hsCRP in all stages of AMD.